Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Problem Solving Terhadap Kemampuan Pemecahan Masalah Soal Cerita pada Materi Statistika Kelas VII SMP Negeri 17 Pontianak - Susan Aza; Rahman Haryadi; Iwit Prihatin (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study aims to develop a Problem Solving-based Student Worksheet (LKPD) to improve problem-solving ability in solving statistics word problems for seventh-grade students at SMP Negeri 17 Pontianak, and to determine its validity, practicality, and effectiveness. The study was motivated by students' low problem-solving ability in statistics word problems, resulting from conventional teaching methods and limited worksheets used in schools. This study employed the Research and Development (R&D) method with a simplified 4D model reduced to a 3D model consisting of define, design, and develop stages. The research subjects consisted of three expert validators (two material experts and two media experts), 24 seventh-grade B students for instrument try-out, and 28 seventh-grade G students for the product try-out. Data were collected through validation sheets, teacher and student response questionnaires, and a problem-solving ability test (posttest), then analyzed descriptively using percentage formulas. The results show that the developed worksheet achieved a validity level of 93.56% (material expert 90.47%; media expert 96.66%), categorized as very valid; a practicality level of 92.45% (teacher response 94%; student response 90.91%), categorized as very practical; and an effectiveness level of 75%, categorized as effective, as shown by 21 out of 28 students achieving mastery learning. Thus, the developed Problem Solving-based worksheet is feasible to be used as an alternative teaching material to improve students' problem-solving ability in mathematics word problems.